Geriatric Nutritional Risk Index Assessment in Patients Undergoing Transcatheter Edge-to-Edge Repair - Kenichi Shibata, PT; Masanori Yamamoto, MD; Ai Kagase, MD; Takahiro Tokuda, MD; Hiroshi Tsunamoto, MD; Testuro Shimura, MD; Azusa Kurita, MD; Ryo Yamaguchi, MD; Mike Saji, MD; Masahiko Asami, MD; Yusuke Enta, MD; Masaki Nakashima, MD; et al. (JACC: Advances)
Background: Transcatheter edge-to-edge repair (TEER) is used to treat patients with mitral regurgitation (MR). The Geriatric Nutritional Risk Index (GNRI) is a well-known nutritional marker that predicts mortality risk. Objectives: The objectives of this study were to elucidate the clinical association between the degree of GNRI and different etiologies of MR and to clarify the patient samples for whom GNRI is more relevant to clinical outcomes following TEER. Methods: Data from 3,554 patients with MR who underwent TEER were analyzed using a Japanese multicenter registry. The patients were classified into 4 groups: GNRI <82, GNRI 82 to 92, GNRI 92 to 98, and GNRI >98. Procedural and clinical outcomes were compared between GNRI groups. Short- and long-term all-cause mortality were explored using Cox regression analysis. Results: Among the 3,554 patients, the median GNRI was 92.3. The mean follow-up period was 586.8 ± 436.5 days; 806 patients died during the follow-up period. Thirty-day mortality occurred in 51 patients (1.4%), and the GNRI <82 group had the highest 30-day mortality rate. Kaplan–Meier curves showed significantly better prognoses for the entire cohort, functional MR, and degenerative MR across the 4 groups (P < 0.001). GNRI values, even after adjustment for multiple confounders, showed a stepwise increase in risk of death in the GNRI 92 to 98, GNRI 82 to 92, and GNRI <82 groups compared to GNRI >98 as the reference. Conclusions: Regardless of MR etiology, GNRI is a useful predictor of short- and long-term mortality in patients undergoing TEER. Although TEER is effective for MR patients in malnourished states, further studies focused on the value of identifying and addressing malnutrition in this population are needed.